2008
DOI: 10.1161/hypertensionaha.108.111054
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Angiotensin Receptor Blocker Valsartan in Children With Hypertension Aged 1 to 5 Years

Abstract: Abstract-The efficacy and safety of valsartan were studied in 90 children (mean age: 3.2 years; 60% male; 30% black) with systolic blood pressure (SBP) Ն95th percentile. Nineteen percent received valsartan in addition to previous antihypertensive therapy. Subjects were randomly assigned to low-, medium-, or high-dose valsartan for 2 weeks (phase 1) and then reassigned randomly to placebo or to remain on the same valsartan dose for 2 additional weeks (phase 2). After this, subjects were enrolled into a 52-week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 21 publications
4
88
0
2
Order By: Relevance
“…Similar results were reported in a study of the ARB valsartan in 90 children aged 1-6 years (4). The authors of this study suggested that young children may be uniquely sensitive to treatment, and a lower starting dose might have facilitated demonstration of a dose response (4). Renin levels are higher in younger children, possibly contributing to greater sensitivity to renin-angiotensin-aldosterone system blockade (11); however, this association could not be tested because renin was not measured in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were reported in a study of the ARB valsartan in 90 children aged 1-6 years (4). The authors of this study suggested that young children may be uniquely sensitive to treatment, and a lower starting dose might have facilitated demonstration of a dose response (4). Renin levels are higher in younger children, possibly contributing to greater sensitivity to renin-angiotensin-aldosterone system blockade (11); however, this association could not be tested because renin was not measured in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Study A2307 6 was performed at 36 centers in 7 countries, and Study A2302 7 was performed at 55 centers in 9 countries. Institutional review boards/ethics committees at each participating center reviewed and approved the study protocols; written informed consent/assent was obtained for all of the study participants according to local requirements.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 In this report we have pooled the baseline clinical and demographic data on the subjects enrolled in those trials to better describe the characteristics of such patients in the current era.…”
mentioning
confidence: 99%
“…They have a powerful, dosedependent antiproteinuric action in pediatric nephropathies (231). RAS inhibitors in general have a favourable side effect profile; however, a few fatalities have been documented in infants with acute intravascular volume depletion while receiving angiotensin receptor blockers (231,232). It is recommended to use RAS blocking agents as first choice with 40 appropriate risk counselling in all proteinuric patients with CKD.…”
Section: Non-diabetic Renal Diseasementioning
confidence: 99%